Effectiveness of horticultural therapy in aged people with depression: A systematic review and meta-analysis - Meijing Xu; Shan Lu; Jianjiao Liu; Feng Xu (Frontiers Media S.A., 2023)
BackgroundDepression, an increasing global crisis, has affected many people's daily life, especially for older adults. Horticultural therapy has been widely used in non-pharmacological treatment for patients with depression, with a body of studies demonstrating its therapeutic effects. However, a lack of systematic reviews and meta-analyses makes it difficult to get a holistic picture of this research field.ObjectivesWe aimed to evaluate the reliability of the previous studies and the effectiveness of horticultural therapy (including the intervention of environmental settings, activities, and duration) on older adults with depression.MethodsThis systematic review was conducted under the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA) guidelines. We searched relevant studies in multiple databases, and the original search was finished on 25 September 2022. We included studies using randomized controlled trials (RCTs) or quasi-experimental designs.ResultsWe yielded a total of 7,366 studies and finally included 13 which involved 698 aged people with depression. Results from meta-analysis indicated significant effects of horticultural therapy on reducing depressive symptoms for the older adults. Besides, we found different outcomes among various horticultural interventions (such as environmental setting, activities, and duration). Depression reduction was more effective in care-providing settings than in community settings; participatory activities were more effective in reducing depression than observational activities; intervention of 4-8 weeks might represent the optimal course of treatment compared to interventions more than 8 weeks in duration.ConclusionWe came up with a comprehensive set of recommendations based on the meta-analysis: aged people in care-providing settings with depression could get the most benefit from horticultural therapy by participating in participatory activities for 4-8 weeks.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022363134, identifier CRD42022363134.